Impact of French Oak Chip Maturation on the Volatile Composition and Sensory Profile of Agiorgitiko Wine - Ioannis Ligas; Yorgos Kotseridis (Beverages)
The traditional practice of aging wines in oak barrels has long been associated with the evolution of wine aromas. However, due to rising costs, alternative approaches like aging with oak chips have gained popularity. The aging time, addition dose, and type of toasting of the oak chips are critical parameters affecting the quality of the wine’s aroma. In this study, we focus on wines from Agiorgitiko variety and explore the impact of oak chip maturation on both volatile composition and sensory profile. By analyzing volatile compounds of wine aroma using GC-MS/MS and conducting descriptive sensory analysis, we investigate the effects of three different oak chip toasting levels, three dosages, and three aging periods. Our findings reveal that almost all wines aged with oak chips exhibit higher ester concentrations compared to the control. Notably, heavily toasted oak chips contribute to the sensory attribute of smoky aroma, while medium oak chips are associated with the sensory attribute of barrel aroma. This study provides valuable data for winemakers to determine the most suitable application for their product.